A series of 1-D, 2-D and 3-D coordination polymers self-assembled from a flexible dicarboxylate and mixed N-donor ligands: syntheses, structural diversity, and luminescent properties. Issue 24 (16th December 2016) - Gao, Yan-Peng; Guo, Le; Lv, Yan-Hua; Dong, Wei; Jia, Min; Chang, Fei
Abstract: We have synthesized a series of metal–organic coordination frameworks under solvothermal conditions, formulated as [Cu(L)(phen)](1 ), [Co2 (L)2 (bib)]·CH3 OH(2 ), [Co(L)(btmb)0.5 ](3 ), [Zn(L)(bib)]·2H2 O(4 ), [Cu(L)(bib)]·DMF(5 ), and [Mn4 (L)4 (bimb)(CH3 OH)](6 ) based on a flexible multicarboxylic bridging ligand 4, 4′-methylenebis(oxy)-dibenzoic acid (H2 L) and flexible N-donor ligands 1, 4-bis (1H-imidazol-1-yl)-butane (bib), 1, 4-bis(1H-1, 2, 4-triazol- 1-ylmethyl)benzene (btmb), and 1, 4-bis(1H-imidazol-1-ylmethyl)benzene (bimb). The structures of the frameworks have been determined by single-crystal X-ray diffraction analyses and further characterized by elemental analyses, IR spectra, and thermogravimetric analyses. The crystal structure determinations reveal that1 has a 1-D Z-shape chain. Compounds2 and3 are 2-D twofold parallel interpenetrating 4-connected net with the Schläfli symbol {4 4 ·6 2 }. Compound4 is a 2-D threefold parallel interpenetrating 4-connected nets with the Schläfli symbol {4 4 ·6 2 }. Compound5 is 3-D 4-connected net with the Schläfli symbol {6 5 ·8}. Compound6 is characterized by a three-dimensional framework with one-dimensional homogeneous Mn-carboxylate chain. We found that flexible carboxylate ligands have different coordination modes under different synthetic conditions. The flexible skeleton of ligands and the coordination angle between the ligand and the metal ion is described. The luminescence and thermogravimetric properties of these compounds have been investigated. Abstract :